Drifting Away from the Mainstream:Media Attention and the Politics of Hyperpartisan News Websites - Yan, P.; Schroeder, R. (Weizenbaum Journal of the Digital Society, 2024)
Populism has recently enjoyed success in Europe, the US, and beyond. Populist leaders and their supporters have accused “mainstream” media of being part of a “corrupt” elite that misrepresents the will of the virtuous “people.” Distrust of the media has also prompted the rejection of traditional media sources for political information and given prominence to alternative and hyperpartisan sources such as Breitbart. However, limited research exists concerning who consumes hyperpartisan media, how the websites of hyperpartisan media are interconnected, and what content is presented in hyperpartisan news. By combining cross-national surveys with large-scale digital trace datasets of website visits, this paper demonstrates the link between populist party support and hyperpartisan media visits. It also identifies influential sources of hyperpartisan news by analyzing the audience similarity networks of these websites and reveals country-level variations in hyperpartisan news and the dominance of US politics among the identified hyperpartisan news topics.